2021
DOI: 10.3390/cells10051252
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glycans on Key Cell Surface Receptors That Regulate Cell Proliferation and Cell Death

Abstract: Cells undergo proliferation and apoptosis, migration and differentiation via a number of cell surface receptors, most of which are heavily glycosylated. This review discusses receptor glycosylation and the known roles of glycans on the functions of receptors expressed in diverse cell types. We included growth factor receptors that have an intracellular tyrosine kinase domain, growth factor receptors that have a serine/threonine kinase domain, and cell-death-inducing receptors. N- and O-glycans have a wide rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 170 publications
(233 reference statements)
0
27
0
Order By: Relevance
“…Sialic acid residues (sialosides) on the cell surface can mediate influenza virus binding and entry into the cell [ 6 ] as they are responsible for intermolecular interactions, particularly in host recognition during bacterial and viral infection [ 7 ]. EGFRs are heavily glycosylated transmembrane proteins with multiple sialic acid residues typically located at the terminal end of glycan structures [ 8 ]. Notably, EGFR has been demonstrated to be a co-receptor for viral infection [ 9 , 10 ] and to transduce signals relevant to virus entry [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sialic acid residues (sialosides) on the cell surface can mediate influenza virus binding and entry into the cell [ 6 ] as they are responsible for intermolecular interactions, particularly in host recognition during bacterial and viral infection [ 7 ]. EGFRs are heavily glycosylated transmembrane proteins with multiple sialic acid residues typically located at the terminal end of glycan structures [ 8 ]. Notably, EGFR has been demonstrated to be a co-receptor for viral infection [ 9 , 10 ] and to transduce signals relevant to virus entry [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we determined that ST6GAL1-mediated sialylation of EGFR prolongs downstream survival signaling by enhancing EGFR retention on the cell surface (24). It is well-known that N-glycans play seminal roles in modulating EGFR structure and signaling (71)(72)(73). For example, an N-glycan attached to Asn-579 is a central player in maintaining the autoinhibitory tether within the EGFR structure (74), and this N-glycan is a known target for sialylation by ST6GAL1 (75).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells usually exhibit altered glycosylation, which is associated with defects in apoptosis [9]. Death receptors such as Fas and DR4/5 are glycoproteins which impact glycosylation during receptor expression, distribution, ligand-receptor interaction, and downstream signaling transduction [9]. Through binding to DR4/5, TRAIL triggers cell death through the extrinsic apoptotic pathway [65].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer progression associated with abnormal glycosylation and these altered glycans regulate a series of pathological processes, including cell-cell interaction, cell adhesion, receptor activation, and signal transduction [8]. Due to the key role of glycosylation in protein expression and transport, ligand binding, and receptor signal transmission [9], the study of its involvement in signal pathway disorders and the development of new strategies to modify cell glycosylation have received significant attention. Recent research has indicated that glycosylation modifications are closely related to HCC, and the upregulation of galactosyltransferase expression was shown to be related to cancer metastasis [10].…”
Section: Introductionmentioning
confidence: 99%